Pengaruh Brand Awareness, Perceived Quality, Brand Association, dan Brand Loyalty Terhadap Brand Equity Hijab SAUDIA (studi kasus pengguna hijab SAUDIA di Soloraya) - Permatasari, Natalia Mila; Rachmawati, Ida Ayu Kade (Indonesian Journal of Strategic Management, 2021)
This research describes the impact of brand awareness, perceived quality, brand association, and brand loyalty on the brand equity of Saudia's hijab. Research uses quantitative types. Taking the illustration required is a non-probability sampling by taking an illustration of 50 respondents to the hijab users in the Soloraya area. The analysis for this research uses multiple linear regression analysis method. The results of this study show that the variable brand awareness and brand association have a significant effect on brand equity of Saudia's hijab, on the other hand, the variables of perceived quality and brand loyalty show that these variables do not affect the brand equity of Saudia's hijab. Based on the results of the analysis, there are some things that must be improved by the Saudia hijab to override the perceived quality variable, namely by improving the quality of the design and the material, and increasing consumer satisfaction and commitment to the Saudia hijab because brand loyalty has a major impact on the brand equity of the Saudia hijab.